2020
DOI: 10.3389/fnins.2020.00430
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses Induced by Manual Therapy in Animal Models: A Scoping Review

Abstract: Background: Physiological responses related to manual therapy (MT) treatment have been investigated over decades using various animal models. However, these studies have not been compiled and their collective findings appraised. The purpose of this scoping review was to assess current scientific knowledge on the physiological responses related to MT and/or simulated MT procedures in animal models so as to act as a resource to better inform future mechanistic and clinical research incorporating these therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 106 publications
1
21
0
Order By: Relevance
“…In animal models, MM induces numerous neurophysiological changes. In fact, MM was associated with modulations in neural, lymphatic, and genetic responses ( Lima et al, 2020 ). For example, abdominal massage improves transit in rats, i.e., reduced time to first fecal discharge in response to mechanical pressures.…”
Section: Manual Massagementioning
confidence: 99%
See 2 more Smart Citations
“…In animal models, MM induces numerous neurophysiological changes. In fact, MM was associated with modulations in neural, lymphatic, and genetic responses ( Lima et al, 2020 ). For example, abdominal massage improves transit in rats, i.e., reduced time to first fecal discharge in response to mechanical pressures.…”
Section: Manual Massagementioning
confidence: 99%
“…For example, abdominal massage improves transit in rats, i.e., reduced time to first fecal discharge in response to mechanical pressures. At the endocrine level, it was also shown that MM reduced the levels of gastrointestinal hormones, i.e., insulin, gastrin and somatostatin ( Lima et al, 2020 ). MM also had modulatory effects at the neural level, since its analgesic effects were associated with changes in descending pain modulation circuits ( Vigotsky and Bruhns, 2015 ).…”
Section: Manual Massagementioning
confidence: 99%
See 1 more Smart Citation
“…Chiropractic manipulation may then modulate the properties of the perceptual-motor workspace of participants. The prevailing thought on the neurophysiological impact of spinal/extremity manipulation is one of perceptual attunement brought about by mechanisms related to greater afferentation by peripheral receptors [33][34][35]; however, our consistent interaction effects suggest the modulation of visual perception may also be a possibility. Furthermore, the action capabilities of the participant are likely promoted by enhanced neural drive through supraspinal, spinal or extremity-based mechanisms [25,36,37].…”
Section: Discussionmentioning
confidence: 59%
“…Chiropractic manipulation may then modulate the properties of the perceptual-motor workspace of participants. The prevailing thought on the neurophysiological impact of spinal/extremity manipulation is one of perceptual attunement brought about by mechanisms related to greater afferentation by peripheral receptors [28][29][30]; however, our consistent interaction effects suggest the modulation of visual perception may also be a possibility. Furthermore, the action capabilities of the participant are likely promoted by enhanced neural drive through supraspinal, spinal or extremity-based mechanisms [20,31,32].…”
Section: Discussionmentioning
confidence: 59%